Trade in the enlarged European Union : a new approach on trade potential - Proença, Isabel (2008)
This paper focuses on the trade potential of manufactured exports from countries belonging to the enlarged EU (EU25) to groups of countries of that economic area in 2002. We note that previous results on trade potential, based on the estimation of a gravity model, may be invalid. Thus, we propose a correct approach based on the Poisson Pseudo-Maximum Likelihood esti- mator and the calculation of confidence intervals with the Delta method. The gravity model includes fixed eff ects to capture bilateral trade specificities be- tween country groupings. We conclude that CEEC as a group had apparently exhausted the possibilities for export expansion in the EU25, unless dynamic changes were to take place. However, several of the remaining EU25 countries had not yet reached their export potential to the EU25 markets, including to the CEEC as a group.